Bibliometric Analysis: The Impact of Using The ELSA Speak Application on Students’ Pronunciation Skills in Articles Indexed By GARUDA - Yossy Fortuna Aprilia; Ika Chairiyani; Rini Septa Angraini (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of research is to determine the development of research, visualization results between keywords, most often used keywords and research trends in studies on the effect of using the ELSA Speak application in improving students’ pronunciation. The research applied the quantitative descriptive method, was conducted used the GARUDA database 2019-2025 based on the main keyword “ELSA Speak.” 28 relevant articles to the research criteria were identified included title, year, author, publisher, publication, and DOI. Data analysis was conducted using Microsoft Excel, Mendeley, and VOSviewer (network visualization, overlay visualization, and density visualization) as bibliometric analysis tools. The research results show that: (1) Research publications on the topic of ELSA Speak from 2019-2025 appear to be unstable each year, with the highest increase of 14 articles in 2024. (2) There are 49 topics divided into 11 clusters and 107 connections between topics. topics such as “Pronunciation,” “ELSA Speak,” and “Speaking skills” are infrequently mentioned in the research. (4) 100% of the ELSA Speak application is effective in improving students’ pronunciation.